POTENSI KANDUNGAN PIGMEN KLOROFIL a DAN b BEBERAPA RUMPUT LAUT GENUS Gracilaria: OPTIMALISASI KANDUNGAN KARBOHIDRAT - Rose Dewi; Dewi Nugrayani; Dyahruri Sanjayasari; Hadi Endrawati (Fakultas Perikanan Dan Ilmu Kelautan Universitas Borneo Tarakan, 2016)
Response pigment and ecological is major factor of photosynthesis. Quantity of chlorophyll a,b are not same in Gracilaria, though in one genus. Difference fluctuation ecological conditions on waters; (Station 1): estuaries, (Station 2): coastal, (Station 3): 100m from the shoreline, based on literature study will affect the rate of photosynthesis. This research aims need to measure of quantitatively pigments (chlorophyll a,b) and carbohydrate to know the difference. Method by purposive random sampling; chlorophyll a,b using UV-Vis spectrophotometer; carbohydrate with analysis by difference; also control physical and chemical parameters of waters. Results show the chlorophyll a, b and carbohydrates in G. verrucosa (163.58 ± 8.90mg /L;79.32 ± 5.53 mg /L; 37.19 ± 1.50%); G. gigas (128.01 ± 7.2 mg /L;117.76 ± 5,85mg /L; 44.48 ± 0.90% ) and G. salicornia (100.36 ± 23.35mg/L; 93.73 ± 11,59mg/L; 36.94 ± 0.72%). The highest correlation between pigments (chlorophyll b) with the formation of carbohydrate in G. gigas (r = 0.991). Range of water quality measured during the study still the threshold that can be tolerated Gracilaria, found only high phosphorus content above the threshold that 1.935 to 2.517 mg/ L.Key words: G. verrucosa, G. gigas, G. salicornia, Chlorophyll a, b , Carbohydrate